Policies for sustainable Development in the highlands of Amhara region: Overview of research findings - Benin, Samuel; Pender, J.L.; Ehui, Simeon K. (Ethiopian Society of Soil Science, 2003)
Reducing resource degradation, increasing agricultural productivity, and reducing poverty and food insecurity are major challenges in Ethiopia, where nearly 90% of people live in rtual areas and depend on agriculture for their livelihoods. Since 1991, the federal and regional governments have focused on promoting conservation of natural resources and improving of agricultural productivity and welfare through a broad program of investment in infrastructure (roads, irrigation, etc.), agricultural extension and credit, education, and other services. Empirical evidence is needed of the impacts of these policies and prodams. Using data from the highlands of Amhara region, this paper addresses the information gap. We find that the agricultural extension program and production of high-value crops have had substantial positive impacts on crop production and household incomes, and have contributed to improved land management and adoption of external inputs. Thus, continuing and expanding the extension approach appears well justified, and promoting production of high-value crops can help households escape the poverty trap. However, a key factor underlying these improvements is road Development (i.e., better access to all-weather roads and markets). Population pressure was associated with lower crop production and incomes, as well as worsening of most resource and welfare conditions. Thus, family planning, education and other means of reducing population growth, as well as developing the non-farm sector, will be crucial in relieving the pressure on the land and raising incomes.